Adaptation Of Architectural Design Features Traditional Malay Houses At Kampung Morten For Malacca Contemporary Houses - RAMLI, NUR IRDINA; SAJI, NURDALILA (Progress in Engineering Application and Technology, 2021)
The application of architectural design features traditional Malay house is an essential approach for the architecture sector in influencing contemporary home. Most contemporary houses are not built by applying traditional heritage design elements due to indifference and less focus on traditional design features. This study aims to identify design features and factors that influence a traditional Malay house at Kampung Morten to Malacca contemporary house. Next to study the structure of a traditional Malay house at Kampung Morten applied in a contemporary house in Malacca and compared the traditional Malay house structure in Kampung Morten against Malacca contemporary house. The methodology was conducted in three methods which are quantitative, qualitative, and through case studies. Survey forms were distributed, and interviews were conducted with Jabatan Perbadanan Muzium Melaka (PERZIM). The data obtained were analysed using Statistical Package for the Social Science (SPSS) software version 25. Inventory forms and case study forms are also used. The researcher can prove the study results that the architectural design features of traditional house structures in Kampung Morten and contemporary houses in categories of roofs, windows wall, pillar, and stair in the physical category can be known in more depth. Contemporary home design should highlight the aspects of moderation of architecture, space and sculptures convey the message design features traditional Malay house easily understandable by the society. In fact, contemporary home design should include the spirit of traditional Malay houses to preserve the Malay heritage and reflects the spirit of cultural identity.